"Increasing Warm Handoffs: Optimizing Community Based Referrals in Primary Care Using QI Methodology". (June 2021) - Sanderson, Dana; Braganza, Sandra; Philips, Kaitlyn; Chodon, Tashi; Whiskey, Renee; Bernard, Patrizia; Rich, Andrea; Fiori, Kevin
Social and environmental factors have an outsized effect on one's health. Children are particularly impacted by the adverse effects of poverty. While social determinants of health (SDH) screening in healthcare settings has proliferated there remain gaps in best practices for screening processes. As research has shown that patient navigation leads to an improvement in unmet social needs and family-reported child health, warm handoffs may be a key factor in assuring that the social needs of families are effectively addressed. Using quality improvement (QI) methods our pediatric clinic worked to increase the warm handoff rate between Community Health Workers (CHWs) and patients with unmet social needs. CHW warm handoff rates increased two-fold over the intervention period. Our results illustrate that QI methods can be used to optimize workflows to increase warm handoffs with CHWs. This is important as health centers work to improve their social needs screening and referral programs.